Ovarian and embryonic response of two superovulation protocols in high Andean Brown Swiss cattle - Allcca Luján, Yeni (2023)
The present study evaluated the ovarian and embryonic response of two hormonal superovulation protocols in high Andean Brown Swiss cattle. Four donor cows were used using an interrupted time series design with switched replications where each cow was subjected to two hormonal superstimulation protocols: protocol 1 (Prot.1, conventional FSH of 400mg in decreasing doses for four days) and protocol 2 (Prot. 2, eCG, 2500IU in a single dose). During the implementation of the protocols, the ovarian evaluation of the preovulatory follicles (POF) and the corpora lutea (CLs) was carried out by ultrasound. Likewise, the quality and rate of recovered embryos were evaluated. The results showed that the number and diameter of FPO and CLs did not show significant differences between the protocols, in the same way the number of embryos collected. With this, it is concluded that both superovulation protocols (FSH and eCG) are applicable in Brown Swiss High Andean cattle. Keywords: high Andean cows, hormonal protocol, FSH, eCG, embryos